Perlindungan Hukum bagi Korban Perdagangan Orang Melalui Media Sosial dalam Perspektif Hak Asasi Manusia - sanseto eriando_hidayat (Jurnal Hukum Lex Generalis, 2025)
Abstract The development of social media has facilitated new modes of human trafficking, creating emerging challenges for victim protection. This study aims to analyze the regulation and implementation of legal protection for human trafficking victims through social media from a human rights perspective in Indonesia. This research employs a normative legal method with statutory and conceptual approaches. The findings reveal that although Indonesia has enacted Law No. 21 of 2007 and other human rights instruments, implementation remains hampered by weak law enforcement, lack of inter-agency coordination, and limited technological adaptation. Regulatory updates and enhanced institutional capacity are essential to ensure effective victim protection.